SANMAI NO OFUDA DALAM PERSPEKTIF GREIMAS - Yuliani Rahmah (Universitas Diponegoro, 2015)
This paper entitled Sanmai no Ofuda in Greimas’s perspective. Sanmai no ofuda is the title of Japan’s folktale has similarities with localfolktales from several regions in Indonesia. In this paper, the writer tried to explain the narrative structure of Sanmai no Ofuda in Greimas’s perspective.Its mean to reveal the narrative structure of this folktale,the writer used structural naratology approaches with Algirdas Julien Greimas’s theory. The writer tried to understand about the intrinsic elements in Sanmai no Ofuda by examining the actans schemes and functional structure. The findings show that the narrative structure can explain the intrinsic elements more specificly.